sVCAM-1 levels in sputum and serum samples of asthmatic patients - (:unkn) unknown (My University, 2001)
There is consisting evidence that asthma is associated with airway inflammation. The role of adhesion molecules in mediating cellular infiltration into the airways continues to be of interest and VCAM-1 (vascular adhesion molecule-1) has been implicated in the eosinophii influx to the lung in asthma. The aim of this study was to evaluate the effect of sVCAM-1 (soluble vascular adhesion molecule-1) in asthma by investigating the serum and sputum levels of sVCAM-1 in asthmatic subjects and healthy controls and to investigate the correlation between disease activity and concentrations of sVCAM-1 in serum and sputum. We evaluated cell profiles and sVCAM-1 in induced sputum samples (with 5% hypertonic saline) and in serum samples of 6 mild, 5 moderate, 7 severe asthmatic patients and 5 healthy controls by using ELISA. The mean concentrations sVCAM in sputum samples of asthmatics and controls were 2.08±1.87 ng/ml and 0.9±2.1 ng/ml, respectively (NS), 15.8±8.9 ng/ml in serums of asthmatics and 9.96+2.35 ng/ml in those of controls (p<0.05). Serum sVCAM-1 levels were statistically higher than those of sputum samples in asthmatics and in controls (p<0.0001 and p<0.008, respectively). Furthermore, serum sVCAM-1 levels decreased as the severity of disease increased in asthmatics, 22.2±12.9 ng/ml in mild, 13.9±1.7 ng/ml in moderate and 10.9±1.7 ng/ml in the severe asthmatic group (p>0.05). FEV, (predicted %) values correlated with serum sVCAM-1 levels in the asthmatic group (p>0.02, r=0.52). We have demonstrated the presence of detectable concentrations of the circulating form of VCAM-1 in sputum samples of both healthy controls and asthmatic patients. The results suggest that measurement of its concentration in serum will be of diagnostic use in asthma and a reflection of the severity of asthmatic airway inflammation.
Keywords: Asthma; Induced sputum; sVCAM-1